Cabinets in Western Europe - Blondel, Jean. author. aut Link
XII, 262 p.
Keywords: A presentation of the structure and workings of the national cabinets in Western European countries today, based on a common framework which enables the reader to compare their origins, structure, composition and activities. Emphasis is placed on the leadership and on the character of coalitions.